Exploring the Potential of Malvidin and Echiodinin as Probable Antileishmanial Agents Through In Silico Analysis and In Vitro Efficacy - Luis Daniel Goyzueta-Mamani; Daniela Pagliara Lage; Haruna Luz Barazorda-Ccahuana; Margot Paco-Chipana; Mayron Antonio Candia-Puma; Gonzalo Davila-Del-Carpio; Alexsandro Sobreira Galdino; Ricardo Andrez Machado-de-Avila; Rodolfo Cordeiro Giunchetti; Edward L. D’Antonio; Eduardo Antonio Ferraz Coelho; Miguel Angel Chávez-Fumagalli (Molecules)
Leishmaniasis, a neglected tropical disease caused by Leishmania species, presents serious public health challenges due to limited treatment options, toxicity, high costs, and drug resistance. In this study, the in vitro potential of malvidin and echioidinin is examined as antileishmanial agents against L. amazonensis, L. braziliensis, and L. infantum, comparing their effects to amphotericin B (AmpB), a standard drug. Malvidin demonstrated greater potency than echioidinin across all parasite stages and species. Against L. amazonensis, malvidin’s IC50 values were 197.71 ± 17.20 µM (stationary amastigotes) and 258.07 ± 17 µM (axenic amastigotes), compared to echioidinin’s 272.99 ± 29.90 μM and 335.96 ± 19.35 μM. AmpB was more potent, with IC50 values of 0.06 ± 0.01 µM and 0.10 ± 0.03 µM. Malvidin exhibited lower cytotoxicity (CC50: 2920.31 ± 80.29 µM) than AmpB (1.06 ± 0.12 µM) and a favorable selectivity index. It reduced infection rates by 35.75% in L. amazonensis-infected macrophages. The in silico analysis revealed strong binding between malvidin and Leishmania arginase, with the residues HIS139 and PRO258 playing key roles. Gene expression analysis indicated malvidin’s modulation of oxidative stress and DNA repair pathways, involving genes like GLO1 and APEX1. These findings suggest malvidin’s potential as a safe, natural antileishmanial compound, warranting further in vivo studies to confirm its therapeutic efficacy and pharmacokinetics in animal models.